Digital brand image management based on feedback loops - N. I. Ivashkova; G. S. Timokhina; I. P. Shirochenskaya (Модернизация, инновация, развитие, 2024)
Purpose: is to propose a model for managing a digital brand image brand based on consecutive feedback loops from the image targetaudience.   Methods: collection, processing, and analysis of secondary data were carried out on the basis of desk research, synthesis methods, contentanalysis, and systemic, structural and functional data evaluation using an interdisciplinary approach.   Results: systemized methodological approaches in Russian and foreign practice by the authors served as the basis for development of a digital brand image management model based on consecutive feedback loops from the image target audience. Within the framework of the proposed model, it is supposed to create systems in a digital environment for providing feedback to the image target audience and monitoring of formed relationships with consumers. The authors' methodological recommendations for implementation of the proposed model are manifested in detailed approaches to organizing the relationship of the image object with the image target audience through different types of feedback loops, methods of monitoring responses and reactions of target consumers, methods of assessing image in a brand's digital environment to close feedback loops.   Conclusions and Relevance: loops of feedback from the brand’s image target audience are a causative mechanism of dynamic nature in which the output data of subjective and objective consumer assessment of brand reputation is used as input data for the management and enhancement of the digital image. Setting up a system of feedback from consumers through digital channels on the basis of consecutive loops allows you to correlate planned indicators of the brand image with the actual indicators, as well as identifi cation of the existing problems and introducing timely adjustments to decisions on managing a brand’s digital image.